Comparative Implementation of School Culture in Senior High Schools: A Case Study of Aceh and West Sumatra - Hariki Fitrah; Muhammad Iqbal; Rambang Muharramsyah (AL-ISHLAH: Jurnal Pendidikan, 2026)
School culture plays a fundamental role in shaping students’ character, learning environment, and educational quality. However, limited research has examined how local cultural values influence the implementation of school culture across different regions in Indonesia. This study aims to compare the implementation of school culture in senior high schools in Aceh and West Sumatra.This study employed a qualitative approach with a comparative case study design. Data were collected from two public senior high schools—SMA Negeri 1 Peusangan (Aceh) and SMA Negeri 3 Payakumbuh (West Sumatra). Participants included principals, teachers, and school supervisors selected באמצעות purposive sampling. Data were gathered through observations and in-depth interviews and analyzed using the Miles and Huberman model, involving data reduction, data display, and conclusion drawing. Trustworthiness was ensured through triangulation and member checking.The findings reveal that both schools successfully integrate school culture through four main dimensions: local cultural practices, literacy culture, environmental awareness (Adiwiyata), and religious culture. While similarities were found in literacy, environmental, and religious programs, differences emerged in the expression of local cultural practices, reflecting each region’s socio-cultural identity. Aceh schools emphasized Islamic traditions and communal rituals, whereas West Sumatra schools highlighted Minangkabau cultural arts and social values. These practices contributed to students’ character development, environmental awareness, and critical thinking.The study highlights that school culture implementation is context-dependent and shaped by local wisdom. Effective school culture requires alignment between national educational goals and regional cultural values to enhance educational quality and sustainability.